Los notarios Pedro Quispe y Pedro de la Carrera: variación lingüística en el Cuzco del siglo XVI - Navarro Gala, Rosario (2016)
In the last twenty Cuzco sixteenth century they exercised their work of public notaries of Pedro Quispe council and Pedro de la Carrera. The first, of Indian origin, left a protocol book that was private affairs of Indians who inhabited the parish of Our Lady of Purificación of Cuzco. Pedro de la Carrera held the same job at the town hall of Cuzco carrying especially the private affairs of the Spanish inhabitants, Creoles and mestizos Cuzco. These two books serve corpus protocol for this study. Based on this documentation it is done to approximate picture of linguistic variation in the city of Cuzco in the last twenty sixteenth century. Linguistic variation we find in the Spanish used by indigenous people with different backgrounds and contrast with Castilian Spanish, Creole and perhaps a mestizo from the same era and city. The documentary corpus employee is original and autograph, and consists of documents belonging to the same discursive tradition, these factors which, if properly harnessed, contribute to the fidelity of the sample.